Synchronous Reluctance Motor: Dynamical Analysis, Chaos Suppression, and Electronic Implementation - Balamurali Ramakrishnan; Andre Chéagé Chamgoué; Hayder Natiq; Jules Metsebo; Alex Stephane Kemnang Tsafack (Complexity)
Dynamical analysis, chaos suppression and electronic implementation of the synchronous reluctance motor (SynRM) without external inputs are investigated in this paper. The different dynamical behaviors (including monostable periodic behaviors, bistable periodic behaviors, monostable chaotic behaviors, and bistable chaotic behaviors) found in the SynRM without external inputs are illustrated in the two parameters largest Lyapunov exponent (LLE) diagrams, one parameter bifurcation diagram, and phase portraits. The three single controllers are designed to suppress the chaotic behaviors found in SynRM without external inputs. The three proposed single controllers are simple and easy to implement. Numerical simulation results show that the three proposed single controllers are effective. Finally, the dynamical behaviors found in the SynRM without external inputs and the physical feasibility of the three proposed single controllers are validated through circuit implementation on OrCAD-PSpice software.